ANALYSIS OF FACTORS THAT AFFECT THE SUCCESS OF WOMEN'S MSME BUSINESSES IN SURABAYA - Ani Suhartatik; P. Julius F. Nagel (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2022)
This study aims to test and analyze the factors that account for the success of women MSME efforts in Surabaya This type of research used is causal research. The sample from this study numbered 84 people using purposive sampling techniques. The data analysis technique used is a multiple regression analysis technique with the SPSS 16.0 program. The results of hypothesis testing showed that the entrepreneurial spirit had no significant positive effect on business success, motivation had a significant positive effect on business success, entrepreneurial competence had a significant positive effect on business success, creativity had a significant positive effect on the success of women's MSME businesses in Surabaya. The implications in this study are that motivation, entrepreneurial competence and creativity have an important role in the success of women’s MSME businesses in Surabaya. Female MSME owners in Surabaya need to increase the spirit of entrepreneurship, increase knowledge and skills to manage the business, be creative about the products offered and creative marketing system because this is able to increase business success.